An Analysis of Slang Used in 13 Going on 30 (2004): Study of Sociolinguistics - Keyza Alifah Mokoginta; Mayzia Sabiha Fidhinillah; Nurlaila Safitri; Aulia Dagna Hasy; M. Eriansyah (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Language functions not only as a medium of communication but also as an essential tool for expressing identity, constructing social relationships, and reflecting cultural values. Within sociolinguistics, slang represents one of the most dynamic and socially meaningful forms of language variation because it conveys informality, emotional intensity, and group belonging. This study examines every slang expression found in the film 13 Going on 30 (2004) by classifying and analyzing each term through Allan and Burridge's (2006) taxonomy of slang. Using a qualitative descriptive method, the researcher identified forty-three slang expressions and analyzed their use in terms of meaning, formation, speaker identity, and sociolinguistic function. The findings reveal that slang in the film reflects early 2000s American youth culture and serves as an expressive tool for identity construction, interpersonal bonding, humor, and informal evaluation. Fresh and creative slang expresses attitude and emotion; flippant slang conveys sarcasm and playful challenge; imitative slang reflects natural spoken patterns; acronym slang demonstrates digital influence; and clipping slang reveals linguistic economy. This study contributes to sociolinguistic scholarship by offering a comprehensive analysis of slang in audiovisual media and showing how linguistic variation supports characterization and cultural atmosphere in film.